Development and Evaluation of Foxnut and Pea Based Functional Biscuits: Nutritional and Organoleptic Perspective - Imran, Aneeza; Fatima, Tuba; Khan, Muneeb; Hanif, Maha; Batool, Saira; Khannum, Usma; Mustafa, Fahad; Abid, Mohsina; Farooqi, Sajal (Biological and Clinical Sciences Research Journal, 2025)
The growing consumer interest in nutritious and functional snacks has driven innovation in bakery products using unconventional, nutrient-dense ingredients. Foxnut and pea flour are promising plant-based sources of protein, fibre, and antioxidants that can enhance the nutritional profile of bakery products. Objective: To develop and evaluate functional biscuits (fox pea sticks) fortified with foxnut and pea flour, assessing their nutritional, physicochemical, and sensory characteristics. Methods: Three biscuit formulations were prepared: T₀ (control, 100% wheat flour), T₁ (5% foxnut + 5% pea flour), and T₂ (10% foxnut + 10% pea flour), sweetened with 1.5% stevia as a sugar substitute. Proximate composition, texture profile (hardness, chewiness, springiness, cohesiveness, resilience), antioxidant activity, and sensory attributes were analyzed over a 14-day storage period. Data were statistically evaluated using ANOVA, with significance set at p < 0.01. Results: Substitution with foxnut and pea flour significantly improved the nutritional quality of the biscuits. Protein, dietary fibre, and antioxidant activity were notably higher in T₁ and T₂ compared to T₀. Texture profiling showed a significant (p < 0.01) increase in hardness, chewiness, and springiness in T₂, reflecting enhanced structural integrity. Sensory evaluation revealed that T₂ achieved the highest scores for appearance, texture, taste, and overall acceptability, indicating superior consumer preference. The T₂ formulation maintained its quality and palatability throughout storage. Conclusion: Incorporation of foxnut and pea flour into wheat-based biscuits successfully enhanced nutritional and functional properties without compromising sensory appeal. The optimized T₂ formulation demonstrated the best balance of texture, nutrition, and acceptability, establishing foxnut and pea flour as sustainable, functional ingredients for health-oriented bakery products.